Immunomodulatory Potential of Piperine in Rats - Alireza Ghavami; Seyyed Meysam Abtahi Froushani; Aliasghar tehrani (Turkish Journal of Immunology)
Objective: The ultimate goal of this research was to investigate the immunomodulatory potential of piperine, a black pepper alkaloid, on innate and acquired immune responses in Lewis rats. Materials and Methods: In the first set of experiments, the effects of a one-month oral administration of piperine on the functions of neutrophils and peritoneal macrophages of Lewis rats were investigated. In a separate set of experiments, the effects of piperine gavage on T helper lymphocyte responses in vivo and ex vivo and their subsets were performed in animals challenged with ovalbumin (OVA). Results: Oral administration of piperine for one month reduced the adhesion of neutrophils (p=0.04). The levels of nitric oxide (p=0.0001) and oxygen free radicals (p=0.003) were significantly decreased in peritoneal macrophages of rats treated orally with piperine for one month. Peritoneal macrophages obtained from rats treated with piperine at doses of 40 and 80 mg/kg for one month significantly produced lower levels of interleukin (IL)-12 after lipopolysaccharide stimulation (p=0.006). IL-10 level was significantly elevated in lipopolysaccharide-primed macrophages isolated from rats receiving piperine for one month (p=0.03). Piperine significantly reduced the intensity of delayed-type hypersensitivity responses in rats immunized with OVA (p=0.003). Ex vivo analysis indicated that oral treatment of piperine increased the expression of GATA3 in OVA-immunized rats (p=0.002). Piperine effectively reduced the expression of T-bet and RORγt mRNA in OVA-immunized rats (p=0.001). Piperine did not alter FOXP3 expression in OVA-immunized rats (p=0.15). Conclusion: These findings show that piperine is a modulating agent of innate and acquired immune responses.